2007
DOI: 10.1037/0022-3514.92.5.905
|View full text |Cite
|
Sign up to set email alerts
|

Ghosts, UFOs, and magic: Positive affect and the experiential system.

Abstract: Three studies examined the potential interactions of the experiential system and positive affect (PA) in predicting superstitious beliefs and sympathetic magic. In Study 1, experientiality and induced positive mood interacted to predict the emergence of belief in videos purporting to show unidentified flying objects or ghosts. In Study 2, naturally occurring PA interacted with experientiality to predict susceptibility to sympathetic magic, specifically difficulty in throwing darts at a picture of a baby (demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 100 publications
4
96
2
Order By: Relevance
“…In other studies, a negative relation has been found between individual's tendency toward analytical thinking and their religious and paranormal beliefs (Aarnio & Lindeman, 2005Gervais & Norenzayan, 2012;King, Burton, Hicks, & Drigotas, 2007;Lindeman & Aarnio, 2006). This suggests that prevalence of System 2 rational processing might be a factor, which promotes disbelief in magical, religious, and paranormal phenomena.…”
Section: The "Fundamentality Hypothesis": Magical Beliefs Reconsideredmentioning
confidence: 97%
“…In other studies, a negative relation has been found between individual's tendency toward analytical thinking and their religious and paranormal beliefs (Aarnio & Lindeman, 2005Gervais & Norenzayan, 2012;King, Burton, Hicks, & Drigotas, 2007;Lindeman & Aarnio, 2006). This suggests that prevalence of System 2 rational processing might be a factor, which promotes disbelief in magical, religious, and paranormal phenomena.…”
Section: The "Fundamentality Hypothesis": Magical Beliefs Reconsideredmentioning
confidence: 97%
“…It should be noted that SM and paranormal beliefs are not always directly linked to experiential processing. King et al (2007) have shown that increased SM, as well as beliefs in UFOs and ghosts, are predicted by dispositional experientiality only when individuals experience positive affect.…”
Section: Cognitive Antecedents Of Romantic Smmentioning
confidence: 99%
“…King et al 2007), involved in PSMS beliefs. The lack of systematic and strong evidence of a link between analytical thinking and PSMS beliefs (e.g., King et al 2007) could be due to its interaction with intuitive processes. However, it may also be the result of methodological issues (Svedholm and Lindeman 2013).…”
Section: Cognitive Antecedents Of Romantic Smmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies of 'positive affect' (PA) and 'faith in intuition' (FI) have predicted superstitious beliefs and sympathetic magic (King et al 2007, Hicks et al 2010 and, thus, are relevant in this study. Like the studies concerning subjective rationality (first identified by William James in 1893), also called the feeling of meaning, which pertains to a feeling about an event or experience which one has found to feel 'right' .…”
Section: Mood and Cognitionmentioning
confidence: 99%